Gastrointestinal parasites in domiciled dogs attended at an animal health service in Rio de Janeiro, Brazil - Leal, Paulo Daniel Sant’Anna; Figueiredo, Laisla Priscila; Moraes, Maria Isabel Menezes Ramos; Barbosa, Larissa Licurci de Oliveira; Figueiredo, Laisla Priscila; Silva, Sheila Lima e; Lopes, Carlos Wilson Gomes (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Leal P.D.S., Moraes M.I.M.R., Barbosa L.L. deO., Figueiredo L.P., Lima e Silva S. & Lopes C.W.G. [Gastrointestinal parasites in domiciled dogs attended at an animal health service in Rio de Janeiro, Brazil.] Parasitos gastrintestinais em cães domiciliados atendidos em serviço de saú- de animal no Rio de Janeiro, Brasil. Revista Brasileira de Medicina Veterinária, 37(Supl.1):37-44, 2015. Curso de Pós-Graduação de Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, Campus Seropédica, BR 465 Km 7, Seropédica, RJ 23890-970, Brasil. E-mail: pauloleal@ctiveterinario.com.br Study of gastrointestinal parasites in pet dogs is a need for veterinary services and public health, as some helminthes, ascomycetes and coccidia are responsible for disease in dogs. This survey aimed to mark the gastrointestinal parasites of pet dogs that looking for a routine of veterinary medical service in the City of Rio de Janeiro. Fecal samples were evaluated through direct examination for the diagnosis of Dipylidium caninum and Giardia intestinalis; whereas centrifugal-flotation technique with Sheater’s solution for diagnosing the presence of helminth eggs and protozoan oocysts respectively. Of 221 samples examined, 92 of them (41.62%) were positive. G. intestinalis cysts were observed in 28 (30.43%) while Ancylostoma caninum eggs in 28 (30.43%) fecal samples were the most frequent infections, followed by Toxocara canis in 6 (6.52%), pseudohyphae of Cyniclomyces guttulatus in 5 of them (5.43%), Cystoisospora canis oocysts in 3 (3.26%), Dipylidium caninum, Sarcocystis spp. in one (1.08%) sample respectively. Multiple infections were observed in stool samples from 20 dogs, where 14 of them showed infection by two etiologic agents consisted of G. intestinalis or A. caninum, following by other associations of A. caninum and D. caninum; G. intestinalis and T. canis; A. caninum and T. vulpis; C. canis and Cystoisospora ohioensis; A. caninum and T. canis; C. canis and T. canis. In four of the fecal samples were observed associations with three parasites as G. intestinalis, C. canis and T. canis; Strongyloides spp., C. canis and C. ohioensis, A. caninum, C. canis and G. intestinalis; G. intestinalis, C. ohioensis and T. canis. With the combination of four etiologic agents in two dogs with G. intestinalis, C. canis, D. caninum and T. canis; A. caninum, C. canis, C. ohioensis and G. intestinalis. Despite the predominance of A. caninum and Giardia intestinalis. should not rule out other gastrointestinal parasites in concomitant infections in dogs. Also, do not forget that some of them cited herein are characterized as zoonotic and common in urban areas in the City of Rio de Janeiro.